The Effect of Visible Light Cure (VLC) Exposure to Gingival Tissue’s Sprague dawley Rats - Kwartarini Murdiastuti; Suryono Suryono; Aini Moeljono; Mefi Priba Sari; Rani Gamawati (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
Visible Light Cure (VLC) is a blue light used in dentistry as an activator for restorative material and fixed orthodontic bonding. The wavelength of VLC is between 400-500 nm and considered non-ionizing radiation that can produce free radicals. According to previous research, the light at wavelength < 500 nm could inhibit cells mitosis, cause cells damage, and reduce cells growth and inflammation. The purpose of this study was to investigate the effect of VLC exposure on gingival epithelial thickness, total neutrophil and macrophage count of gingival connective tissue of Sprague dawley rats. The subjects of this study consisted of 20 Sprague dawley rats, in 2-3 months of age and divided into 4 groups. Each group was 5 rats. The rats in each group were sacrificed before (0 day, as group A) and after 1st (group B), 3rd (group C), 5th (group D) day of VLC exposure, respectively. The exposure of VLC was done in labial aspect of cervical anterior teeth of mandible. The distance of exposure was as thick as 2 layers of celluloid strip and the histological specimens were stained by Hematoxylin Eosin. Each specimen was measured for its gingival epithelial thickness by using a micrometer and the number of neutrophil and macrophage were counted. The data of gingival epithelial thickness from 4 groups were analyzed by Kruskal Wallis. The number of neutrophil and macrophage were analyzed by u sing one way ANOVA. The results of this study showed that there were significant differences among groups on the thickness of gingival epithelial, the number of neutrophil and macrophage in the gingival connective tissue of Sprague dawley rats. The result of this study indicated that VLC exposure might decrease the thickness of gingival epithelial but increase the number of neutrophil and macrophage of gingival connective tissue of Sprague dawley rats.